2016
DOI: 10.1007/s10549-016-3755-6
|View full text |Cite
|
Sign up to set email alerts
|

Is ultrasound-guided fine-needle aspiration cytology of adequate value in detecting breast cancer patients with three or more positive axillary lymph nodes?

Abstract: This study evaluated the accuracy of ultrasound-guided fine-needle aspiration cytology of the sonographically most suspicious axillary lymph node (US/FNAC) to select early breast cancer patients with three or more tumour-positive axillary lymph nodes. Between 2004 and 2014, a total of 2130 patients with histologically proven early breast cancer were evaluated and treated in the Noordwest Clinics Alkmaar. US/FNAC was performed preoperatively in all these patients. We analysed the results of US/FNAC retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…The metaanalysis by van Wely et al [29] shows that 56% of the patients with positive A-FNAC have three or more positive ALNs, and the other big study by G.M. Kramer et al [30] shows almost identical numbers, with a positive predictive value (PPV) of 58%. These patients could probably benefit from additional axillary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The metaanalysis by van Wely et al [29] shows that 56% of the patients with positive A-FNAC have three or more positive ALNs, and the other big study by G.M. Kramer et al [30] shows almost identical numbers, with a positive predictive value (PPV) of 58%. These patients could probably benefit from additional axillary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The routine use of preoperative ultrasonography of the axilla in combination with fine‐needle aspiration cytology (US/FNAC) of regional lymph nodes was not reported in the studies that found extensive nodal metastatic involvement in patients with nonvisualization on preoperative imaging . Kramer et al demonstrated that preoperative US/FNAC has an adequate accuracy of 89.8% to detect three or more positive lymph nodes. After US/FNAC, most of the patients with extensive nodal metastatic involvement would not undergo a SLNB procedure.…”
Section: Introductionmentioning
confidence: 99%
“…USG-FNAC is widely utilized to investigate enlarged or abnormal lymph nodes in BC patients [19, 20]. The technique has been shown to have good diagnostic accuracy, with a sensitivity of 65–99% and a specificity of 80–100% [21]; to detect ≥3 positive nodes, sensitivity was 44.8%, specificity 95.7%, PPV 58.1%, and NPV 92.9% [20].…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been shown to have good diagnostic accuracy, with a sensitivity of 65–99% and a specificity of 80–100% [21]; to detect ≥3 positive nodes, sensitivity was 44.8%, specificity 95.7%, PPV 58.1%, and NPV 92.9% [20]. Rapid on-site evaluation of ALNs in aspirated specimens has been shown to be diagnostically helpful [21, 22].…”
Section: Discussionmentioning
confidence: 99%